A study of role of diagnostic and therapeutic laparoscopy in chronic and recurrent abdominal pain - Karvande, Rajeev; Kamble, Ranjeet; Kharade, Manoj (International Surgery Journal, 2016)
Background:Chronic abdominal pain is a common complaint of the patients seeking a primary care physician. It leads to evident suffering and disability, both physically and psychologically and it is associated with poor quality of life. Many diagnostic and therapeutic procedures have been described in literature, in that laparoscopy is one of the modalities that could be of benefit in such cases. Hence, the aim of the study was to evaluate the role of diagnostic and therapeutic laparoscopy in chronic and recurrent idiopathic abdominal and also to assess the epidemiology, clinical features, diagnostic modalities and management of chronic and recurrent abdominal pain. Methods: This is a single centre, prospective study done on 63 patients with chronic abdomen pain. The pain in all patients was of unknown etiology despite all the investigative procedures. All patients were subjected to laparoscopic evaluation for their conditions. The findings and outcomes of the laparoscopy were recorded and analyzed. Results:In the present study Out of 63, 26 were male 37 were female showing female preponderance (58.7%) of patients presenting with chronic and recurrent abdominal pain with mean age of presentation 31.7 years. The majority of the patients in our study presented with pain in right lower quadrant pain (n=43) followed by pain in periumbilical region (n=7). Others had pain in other quadrants of abdomen. Only 6 patients had diffuse abdominal pain. In our study of 63 patients, the most common finding was chronic appendicular pathology, which was present in 56.1% patients, inflammatory or congenital band of adhesions noted in around 21.2 % patients, abdominal Koch’s was noted in 19.7%, mesenteric lymphadenopathy noted in around 18.2%, ovarian cyst findings were noted in around 7.6% patients, 2 patients had Meckel’s diverticulum and 4 had normal findings. 92.08% (n=58) patients had positive response (Reduction or complete relief of pain) at the end of one month in relation to effectiveness of diagnostic laparoscopy combined with a therapeutic procedure while 88.88% (n=56) had positive response at the end of two months. Conclusions:Laparoscopy is a safe, quick and effective modality of investigation for chronic abdominal pain. Not only does laparoscopy point to a diagnosis, it has the added advantage that therapeutic intervention can be done at the same sitting in most cases thus avoiding another hospitalization or another exploration of the abdomen. Diagnostic laparoscopy has a high diagnostic and therapeutic efficacy.